Epidemiological analysis of serological markers of hepatitis B in HIV+ patients from Curitiba and metropolitan region - Aline C. Vieira; Maria R. P. A. Tizzot; Vera L. P. Santos; Fernanda Bovo; Iara M. Reason (Jornal Brasileiro de Patologia e Medicina Laboratorial, 2015)
Introduction: The presence of hepatitis B virus (HBV) in patients infected by the human immunodeficiency virus (HIV) leads to a higher incidence of liver disorders due to persistence and recurrence of HBV infection in addition to increased morbidity and mortality. Objective: To determine the prevalence of serological markers for hepatitis B in patients infected by HIV followed at Hospital de Clínicas da Universidade Federal do Paraná (HC-UFPR). Methods: The clinical and epidemiological data were collected through a questionnaire applied to the patients, as well as a retrospective analysis of medical records. Serum levels of total hepatitis B core antibody (anti-HBc) and surface antigen of the hepatitis B virus (HBsAg) were evaluated through chemiluminescent microparticle immunoassay. Among the 297 HIV+ patients, 49.8% were seropositive only for anti-HBc, and 2.6 % were positive for both markers. Results and discussion: The prevalence of hepatitis B markers was significantly associated with HIV infection when compared with the prevalence observed in the general population from the same geographical area (anti-HBc+ HBsAg+: 0.14% vs. 2.6%, OR: 18.82, 95% CI 2.34-151.19, p = 0.00052). Concerning the associated risks to acquire HIV/HBV infection, 44.87% of the patients reported having been infected through sexual contact. A total of 16.66% HIV/HBV positive patients were in the age group 18-30 years, 62.82% were between 31-50 years and 16.66% were over 60 years old. Conclusion: The findings of the present study corroborate the need to investigate systematically the presence of markers for HBV in HIV+ patients from different regions of the country.